The importance of small-island populations for the long-term survival of endangered large-bodied insular mammals - Sabhrina Gita Aninta; Rosie Drinkwater; Alberto Carmagnini; Nicolas J. Deere; Dwi Sendi Priyono; Noviar Andayani; Nurul L. Winarni; Jatna Supriatna; Matteo Fumagalli; Greger Larson; Peter H. A. Galbusera; Alastair Macdonald; et al. (Proceedings of the National Academy of Sciences, 2025)
Island populations of large vertebrates have experienced higher extinction rates than mainland populations over long timescales due to demographic stochasticity, genetic drift, and inbreeding. While being more susceptible to extinction and as such potentially targeted for conservation interventions such as genetic rescue, small-island populations can experience relatively less anthropogenic habitat degradation than those on larger islands. Here, we determine the consequences and conservation implications of long-term isolation and recent human activities on genetic diversity of island populations of two forest-dependent mammals endemic to the Wallacea archipelago: the anoa ( Bubalus spp.) and babirusa ( Babyrousa spp.). Using genomic analyses and habitat suitability models, we show that, compared to closely related species, populations on mainland Sulawesi exhibit low heterozygosity, high inbreeding, a high proportion of deleterious alleles, and experience a high rate of anthropogenic disturbance. In contrast, populations on smaller islands occupy higher-quality habitats, possess fewer deleterious mutations despite exhibiting lower heterozygosity and higher inbreeding. Site frequency spectra indicate that these patterns reflect stronger, long-term purging in smaller-island populations. Our results thus suggest that conservation efforts should focus on protecting small-island high-quality habitats and avoiding translocations from mainland populations. This study highlights the crucial role of small offshore islands for the long-term survival of Wallacea’s iconic and indigenous mammals in the face of development on the mainland.